2012
DOI: 10.7150/jca.4542
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Assessing the Potential Role of non-CD133 Colorectal Cancer Stem Cells as Biomarkers

Abstract: Introduction: Over 50% of patients with colorectal cancer (CRC) will progress and/or develop metastases. Biomarkers capable of predicting progression, risk stratification and therapeutic benefit are needed. Cancer stem cells are thought to be responsible for tumor initiation, dissemination and treatment failure. Therefore, we hypothesized that CRC cancer stem cell markers (CRCSC) will identify a group of patients at high risk for progression.Methods: Paraffin-embedded tissue cores of normal (n=8), and histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 41 publications
5
42
2
4
Order By: Relevance
“…After 59 months of follow-up, epcam-positive disseminated tumour cells were found to be significantly associated with overall survival and recurrence-free survival, and with a high density of peritumoural lymphatic vessels. In another study of 40 patients (30 primary, 10 metastatic), lymph node metastases were found to be associated with a trend toward decreased expression of epcam (p = 0.06) 27 .…”
Section: Discussionmentioning
confidence: 99%
“…After 59 months of follow-up, epcam-positive disseminated tumour cells were found to be significantly associated with overall survival and recurrence-free survival, and with a high density of peritumoural lymphatic vessels. In another study of 40 patients (30 primary, 10 metastatic), lymph node metastases were found to be associated with a trend toward decreased expression of epcam (p = 0.06) 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The literature data show that high ALDH1 expression is associated with high tumor grade and bad prognosis of disease [Langan et al 2012;Chen et al 2015].…”
Section: Prognostic and Predictive Stemness Biomarkersmentioning
confidence: 99%
“…ALCAM expression is very variable in CRC tissues; moreover, its overexpression has been associated with shortened OS and poor patient prognosis. The use of ALCAM to identify a CD44+/EpCAM+ subpopulation of cancer cells has also been suggested [Lugli et al 2010;Tachezy et al 2012;Langan et al 2012].…”
Section: Prognostic and Predictive Stemness Biomarkersmentioning
confidence: 99%
“…The characteristics of the isolated cells were first evaluated by flow cytometry using CD markers to identify potential stem cells. CD105 (endoglin) is a member of the transforming growth factor beta family, which has been linked with multi-lineage differentiation capacity [9], while CD29 (integrin beta 1) is responsible for mediating cell-to-cell adhesion and is involved in cell growth, differ- [10]. CD90 (Thy-1) is expressed in colony forming cells with high proliferative potential and is also used to characterize stem cell populations.…”
Section: Characterization Of Mastoid Bone Marrow-derived Cellsmentioning
confidence: 99%